Representation of women in advertisements in Arabic and English magazines: a multimodal critical discourse approach - Altuwaijri, Nada (2020)
This thesis is concerned with investigating the representations of ideal femininity in cosmetics’ advertising discourse in two versions of ELLE print magazine, ELLE ARABIA and ELLE UK. It also aims at examining the linguistic and semiotic persuasive strategies advertisers employ to construct such ideals. Moreover, it investigates the readers’ perspectives and perceptions of cosmetics advertisements. Thus, a triangulated method is applied to the data: Multimodal Critical Discourse Analysis (MCDA), Critical Discourse Analysis (CDA) and focus groups. MCDA and CDA are applied to the dataset of advertising discourse to cross-culturally examine the ideal feminine figure and female identities presented in the data, while focus groups are conducted to elicit readers’ perceptions of the adverts’ content.